Implementation of Justice Collaborators’ Rights in Obtaining Reduced Sentences in Murder Cases - Dany Ardiansah Putra; Siti Marwiyah; Sukmana Dumayanti; Hartoyo; Bachrul Amiq (PT. Banjarese Pacific Indonesia, 2026)
The rights of justice collaborators (JCs) to obtain sentence reductions in murder cases remain inconsistently applied within Indonesia’s criminal justice system. This research addresses three core issues: the normative legal basis for JC rights, the consistency of judicial decisions in granting those rights, and the necessity for legal reform. Using a normative juridical approach supported by document analysis and expert interviews, the study examines Law No. 31/2014, SEMA No. 4/2011, and recent judicial decisions, including the high-profile cases of Richard Eliezer and Abdul Khoir. Findings reveal that while legal provisions exist, the absence of detailed indicators, formal mechanisms for status determination, and binding multi-institutional coordination leads to implementation gaps. Judicial discretion remains unchecked, resulting in unequal treatment of justice collaborators with similar contributions. The study concludes that a lex specialis law is urgently needed to standardize definitions, evaluation mechanisms, and inter-agency protection schemes. Recommendations include harmonization of technical norms, incorporation of JC recognition in verdicts, and alignment with UNCAC and UNTOC standards. This would strengthen legal certainty, uphold the principle of nulla poena sine lege, and enhance the effectiveness of the criminal justice system in addressing serious crimes through systemic cooperation.